Comprehensive Comparative Analysis of Mobile Apps Development Approaches - Gerges, Maher; Elgalb, Ahmed (Journal of Artificial Intelligence General science (JAIGS) ISSN:3006-4023, 2024)
Growing use of the cell phones and tablets over the computer for humans’ daily life has increased the development of mobile apps. Different paradigms have been introduced to develop a mobile app. Up till now, the major paradigms have been introduced are native apps, hybrid apps, web app and the new trend namely progressive web app (PWA). Each methodology has its pros and cons. This paper discusses about native development issues and how web app aimed to solve these problems. The hybrid apps will be discussed as a solution of cross-platform development problem of native apps. In addition, problems of web apps and the gap between web app and native apps will be introduced. PWA is supposed to bridge the gap between native apps and web apps. The main technologies –service worker- will also be discussed.